BACTERIAL PROFILE, ANTIBIOTIC SENSITIVITY AND RESISTANCE OF LOWER RESPIRATORY TRACT INFECTIONS IN UPPER EGYPT - Gamal Agmy; Sherif Mohamed; Yaser Gad; Essam Farghally; Hamdy Mohammedin; Hebba Rashed (Mediterranean Journal of Hematology and Infectious Diseases)
BACKGROUND: Lower respiratory tract infections (LRTI) account for a considerable proportion of morbidity and antibiotic use. We aimed to identify the causative bacteria, antibiotic sensitivity and resistance of hospitalized adult patients due to LRTI in Upper Egypt. METHODS: A multicentre prospective study was performed at 3 University Hospitals for 3 years. Samples included sputum or bronchoalveolar lavage (BAL) for staining and culture, and serum for serology. Samples were cultured on 3 bacteriological media (Nutrient, Chocolate ,MacConkey's agars).Colonies were identified via MicroScan WalkAway-96. Pneumoslide IgM kit was used for detection of atypical pathogens via indirect immunofluorescent assay. RESULTS: The predominant isolates in 360 patients with CAP were S.pneumoniae (36%), C. pneumoniae (18%), and M. pneumoniae (12%). A higher sensitivity was recorded for moxifloxacin, levofloxacin, macrolides, and cefepime. A higher of resistance was recorded for doxycycline, cephalosporins, and β-lactam-β-lactamase inhibitors. The predominant isolates in 318 patients with HAP were, methicillin-resistant Staphylococcus aureus; MRSA (23%), K. pneumoniae (14%), and polymicrobial in 12%. A higher sensitivity was recorded for vancomycin, ciprofloxacin, and moxifloxacin. Very high resistance was recorded for β-lactam-β-lactamase inhibitors and cephalosporins. The predominant organisms in 376 patients with acute exacerbation of chronic obstructive pulmonary diseases (AECOPD) were H. influnzae (30%), S. pneumoniae (25%), and M. catarrhalis(18%). A higher sensitivity was recorded for moxifloxacin, macrolides and cefepime. A higher rate of resistance was recorded for aminoglycosides and cephalosporins